Surgical Treatment of Pulsatile Tinnitus Caused by the Sigmoid Sinus Diverticulum. Issue 21 (May 2015) - Wang, Guo-Peng; Zeng, Rong; Ma, Xiao-Bo; Liu, Zhao-Hui; Wang, Zhen-Chang; Gong, Shu-Sheng; Lin., Yung-Song
<x xml:space="preserve">Abstract</x> Abstract The sigmoid sinus diverticulum (SSD) is an increasingly recognized cause of pulsatile tinnitus (PT). Surgical reconstruction of the sigmoid sinus wall has been found to be highly effective for SSD; however, surgical techniques still need to be refined to reduce the incidence of serious postoperative complications. Moreover, scrutinizing more cases of SSD is desirable for establishing the diagnostic criteria and standardizing the surgical technique. This study was retrospectively undertaken in 28 patients who were diagnosed with SSD upon computed tomography angiography (CTA) and digital subtraction angiography findings at Beijing Tongren Hospital in China. A majority of patients (20/28) presented with SSD and accompanying sigmoid sinus wall dehiscence (SSWD). Twenty-five patients opted to undergo sigmoid sinus wall reconstruction, and 3 patients refused surgery. Following surgery, 17 patients experienced complete resolution of PT, 3 patients experienced partial resolution, and 5 patients experienced no change in PT. No serious complications were found postoperatively. A comparative analysis of the preoperative and postoperative CTA findings suggested that completely resolving SSD and the accompanying SSWD resulted in the elimination of PT. In conclusion, SSD is generally accompanied by SSWD. Sigmoid sinus wall reconstruction is a safe and effective approach for the treatment of SSD. During surgery, completely resolving both SSD and SSWD is advisable, and maintaining the normal diameter of the sigmoid sinus is imperative.